(x*x)=-5x+24

Simple and best practice solution for (x*x)=-5x+24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x*x)=-5x+24 equation:


Simplifying
(x * x) = -5x + 24

Multiply x * x
(x2) = -5x + 24
x2 = -5x + 24

Reorder the terms:
x2 = 24 + -5x

Solving
x2 = 24 + -5x

Solving for variable 'x'.

Reorder the terms:
-24 + 5x + x2 = 24 + -5x + -24 + 5x

Reorder the terms:
-24 + 5x + x2 = 24 + -24 + -5x + 5x

Combine like terms: 24 + -24 = 0
-24 + 5x + x2 = 0 + -5x + 5x
-24 + 5x + x2 = -5x + 5x

Combine like terms: -5x + 5x = 0
-24 + 5x + x2 = 0

Factor a trinomial.
(-8 + -1x)(3 + -1x) = 0

Subproblem 1

Set the factor '(-8 + -1x)' equal to zero and attempt to solve: Simplifying -8 + -1x = 0 Solving -8 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -1x = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -1x = 0 + 8 -1x = 0 + 8 Combine like terms: 0 + 8 = 8 -1x = 8 Divide each side by '-1'. x = -8 Simplifying x = -8

Subproblem 2

Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3

Solution

x = {-8, 3}

See similar equations:

| Y/-3 | | 4y=33.2 | | 9x+8.1=-0.9 | | 4y-5+y+21=6y+20-3y | | -13=(4/11)4+b | | 4x^3+12x^2-72=0 | | -4-17= | | 8(t+5)+15= | | (5a^-6/3b^-8)^4 | | a=2bcd*c | | -6t+14=2 | | y/7=10 | | X^3+3x^2-18=0 | | 8r-14=-28+r | | 0=(1/10)10+b | | 6+4.3-2= | | -2x(x+4)=2(-2x-8)+5x | | 9(4-2)+15= | | a=2bcd | | x^2+9x-2=8x+10 | | -10*8= | | 11=(15/17)8+b | | 25*2+x=154 | | 9n-4=40 | | 4+3(x+5)= | | -10x+12=2(-2x-8)+5x | | m+n=-4 | | 5+3-2.2= | | -x+4x=5(3)+2 | | 15x-6-15x=6 | | t^2=-16-10t | | 3x^2-3x=216 |

Equations solver categories